Push‐Pull Bis‐Norbornadienes for Solar Thermal Energy Storage - Weber, Roza R.; Stindt, Charlotte N.; Harten, A M. J.; Feringa, Ben L. (Chemistry : a European journal, 2024)
The norbornadiene/quadricyclane (NBD/QC) photoswitch pair represents a promising system for application in molecular solar thermal energy storage (MOST). Often, the NBD derivatives have very limited overlap with the solar spectrum, and substitution to redshift the absorption leads to a decrease in the gravimetric energy density. Dimeric systems mitigate this factor because two switches can ‘share’ a substituent. Here, we present five new NBD dimers with red‐shifted absorption spectra. One dimer features the most red‐shifted absorption onset (539 nm) and a significantly red‐shifted absorption maximum (404 nm) for NBD systems reported so far, without compromising thermal half‐life. Promising properties for high‐performance MOST applications are demonstrated, such as high absorption onsets reaching 539 nm, and energy densities of 379 kJ/kg, while still maintaining long half‐lives of the metastable isomer, up to 23 hours at 25 °C. Not only the production, but especially the storage of renewable energy is crucial for a sustainable society. A major challenge in the field of molecular solar thermal energy storage is designing visible light‐absorbing photoswitches with long energy storage half‐lives. Five novel visible light‐absorbing norbornadiene dimers were prepared, with half‐lives up to 23.0 hours, and high energy densities up to 379.3 kJ/kg.